Inovasi dan Kolaborasi Perpustakaan Perguruan Tinggi di Indonesia dalam Mendukung Roadmap Making Indonesia 4.0 - Vilianty Rizki Utami; Madiareni Sulaiman (Perpustakaan Nasional, 2022)
With the rapid development of technology, libraries, especially in higher education or university, as service providers need to innovate and collaborate. This research focuses on identifying innovations and collaboration of academic libraries (Perpustakaan PT) in supporting the Making Indonesia 4.0 Roadmap initiated by the Ministry of Industry. The framework of this research is based on the future library trend model designed by the American Library Association (ALA), with a qualitative approach, where the stages of data collection are carried out through desk research activities. Based on the findings of this study, there are 37% of Perpustakaan PTs who have owned or developed innovations according to the innovation trend grouping of the Future of Libraries ALA, where 12% of them have carried out internal collaborations and the other 13% have collaborated internally and externally with institutions (703 Perpustakaan PTs). Academic libraries need to increase their capacity in innovation and collaboration and library supervisors also need to pay attention to the inequality of innovation in various regions in Indonesia, which are more dominated by the Java region. Moreover, based on a survey of most PT libraries, it was found that several points in the future ALA library model had not been realized properly, such as points related to technology, government politics and demography.